Intramuscular vaccination with Strangvac is safe and induces protection against equine strangles caused by Streptococcus equi. Issue 31 (26th June 2020) - Robinson, Carl; Waller, Andrew S.; Frykberg, Lars; Flock, Margareta; Zachrisson, Olof; Guss, Bengt; Flock, Jan-Ingmar
Highlights: Strangvac was safe when administered via intramuscular injection. Strangvac induced elevated systemic and mucosal antibody responses. Vaccination with Strangvac did not interfere with a commercial iELISA. Strangvac conferred significant levels of protection after two or three vaccinations. Abstract: The equine disease strangles, caused by Streptococcus equi, remains a major cause of welfare and economic cost to the global horse industry. Here we report the safety, immunogenicity and efficacy of a novel multi-component chimeric fusion protein vaccine, called Strangvac, when administered to ponies via the intramuscular route. Across the four studies, Strangvac was safe and induced robust antibody responses towards the vaccine components in blood serum and the nasopharynx, which were boosted by revaccination up to 12 months after a primary course of 2 vaccinations 4 weeks apart. The vaccine response did not cross-react with a commercial strangles iELISA, which identifies horses that have been exposed to S. equi, demonstrating that it was possible to differentiate infected from vaccinated animals (DIVA). Following challenge with S. equi strain 4047 ( Se 4047), all 36 control ponies that had received an adjuvant-only placebo vaccine developed clinical signs of strangles. In contrast, intramuscular vaccination with Strangvac protected ponies significantly from challenge with Se 4047 at two weeks (5 of 16 ponies protected (31%), P  = 0.04) and two months (7 of 12 ponies protected (58%), P  = 0.0046 (including pooled control data) after second vaccination. Optimal protection (15 of 16 ponies protected (94%), P  < 0.0001) was observed following challenge at two weeks post-third vaccination. Our data demonstrate that Strangvac is safe, has DIVA capability and provides a rapid onset of protective immunity against strangles. We conclude that Strangvac is a valuable tool with which to protect horses from strangles, particularly during high-risk periods, whilst maintaining the mobility of horse populations as required by the global equine industry.